2021
DOI: 10.3390/app11167603
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Analysis of the Impact of Cylinder Deactivation on Fuel Saving and Emissions of a Medium-Speed High-Power Diesel Engine

Abstract: The potential benefit of cylinder deactivation (CDA) on power and emission performances has been numerically investigated on a locomotive 16-cylinder diesel engine. A 1D model combined with a predictive friction model and a 3D combustion model based and validated on experimental data have been developed to simulate engine working processes by deactivating half of the cylinders by cutting off the fuel supply and maintaining/cutting off valve motions. The results demonstrate that CDA with the valves closed decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…But these emissions never fell below their baseline levels, since formation was still greater than oxidation, except in the case of CO emission at CDA operation. However, several experimental studies have demonstrated that soot, HC and CO emissions can be cut by more than 50 % in CDA and CCO by increased oxidation, high air fuel ratio (AFR) and increased injection pressure [57,58].…”
Section: Effect Of Cylinder Deactivation (Cda) and Cylinder Cut-out (...mentioning
confidence: 99%
“…But these emissions never fell below their baseline levels, since formation was still greater than oxidation, except in the case of CO emission at CDA operation. However, several experimental studies have demonstrated that soot, HC and CO emissions can be cut by more than 50 % in CDA and CCO by increased oxidation, high air fuel ratio (AFR) and increased injection pressure [57,58].…”
Section: Effect Of Cylinder Deactivation (Cda) and Cylinder Cut-out (...mentioning
confidence: 99%
“…For this reason, an approach that couples 1D and 3D is being used to analyze the gas flow in the CI engine. Liu et al analyzed the effect of cylinder deactivation on fuel saving and emission by coupling the 1D model and the 3D combustion model and verified the accuracy by comparing the experiment and the results [17]. Wurzenberger simulated SCR by coupling 1D and 3D approaches and proposed a method that can be used to support design decisions and to shorten the overall development process of SCR systems [18].…”
Section: Introductionmentioning
confidence: 99%